PANTHEISM OF KNOWLEDGE IN THE PHILOSOPHY OF ABU NASR FARABI (Scientific journal of the Fergana State University, 2023)
The scientist of the early Renaissance, the genius Abu Nasr Farabi, revived ancient Greek philosophy, enriched it with new philosophical theories and conclusions, created Eastern Muslim philosophy. He created a unified and logically complete philosophical thinking. He based it on a person and his creative activity. Man as the cause of all creatures created by God, His behavior manifests itself in the mind inherent only in humanity. This article describes the expression of knowledge in the philosophy of Farabi. We can see his pantheistic views in the theoretical analysis of reason.